Apuntes para una historia del Boletín de Antropología de la Universidad de Antioquia (1953-2013) (2013)
ABSTRACT: This article highlights key moments in the history of the Boletin de Antropología, a journal edited by the Anthropology Department at the University of Antioquia and which began under the inspiration of Graciliano Arcila Vélez in 1953. Three moments are mentioned in this accounting: the consolidation phase (1953-1970), the versatile permanence phase (1974-1994), and the standardization and internationalization phase (1995-2013).